The Thrombostat System A Useful Method to Test Antiplatelet Drugs and Diets - Kratzer, Michael AA; Negrescu, Emil V; Hirai, Azan; Yeo, Young K; Petra, Franke; Siess, Wolfgang (Seminars in Thrombosis and Hemostasis, 1995)
The use of platelet inhibitory drugs, like aspirin, has resulted in a significant reduction of thrombotic complications in primary and secondary prevention of heart attacks. To find more effective substances or better drug combinations, inhibition of primary hemostasis in vitro (Thrombostat system) was investigated, with different drugs and fish diet, using small samples (1 ml) of anticoagulated (Na- citrate 3.8%, 1/9) human blood. Results: 1. In the presence of 1mM aspirin, which had no effect on bleeding volume, only 0.6 nM iloprost were necessary to show a 50% inhibition, in contrast to 2.5 μM without aspirin. 2. At aspirin concentrations of 1 mM, 50% inhibition of primary hemostasis could be achieved with 20 μM SIN-I, or with 7 μM SIN-l together with iloprost (500 pM). The same effect was seen only with very high doses of SIN-l (1000 μM) alone. 3. For 50% inhibition of primary hemostasis in vitro, RGDS concentrations were reduced from 250 μM to 160 μM when blood was pretreated with 1 mM aspirin and to 75 μM when 500 pM i1oprost were added additionally. 4. Japanese fishermen (eating 270 g fish/day) demonstrated significantly longer in-vivo bleeding times and in-vitro bleeding volumes (6.49 min/224 μI), respectively, as compared to Japanese farmers (90g fish/day, 4.85 min/137 μI). 5. In Japanese subjects in-vivo bleeding times correlated with in-vitro bleeding volumes (0.69). The Thrombostat system proved to be a sensitive method to detect synergistic effects of various antiplatelet drugs in vitro and of a platelet inhibitory diet ex vivo.
Keywords: primary hemostasis; bleeding time; platelet aggregation; aspirin; fish diet; Thrombostat